2000
DOI: 10.1099/0022-1317-81-9-2327
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of prion protein in the ileal Peyer’s patch of scrapie-free lambs and lambs naturally and experimentally exposed to the scrapie agent

Abstract: A sensitive immunohistochemical procedure was used to investigate the presence of prion protein (PrP) in the ileal Peyer's patch of PrP-genotyped lambs, including scrapie-free lambs and lambs naturally and experimentally exposed to the scrapie agent. The tyramide signal amplification system was used to enhance the sensitivity of conventional immunohistochemical procedures to show that PrP was widely distributed in the enteric nervous plexus supplying the gut wall. In scrapie-free lambs, PrP was also detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 57 publications
5
101
0
Order By: Relevance
“…In sheep, PrP Sc or scrapie infectivity is present primarily in tissues of the central and peripheral nervous system, lymphoreticular system, and placenta (9,(14)(15)(16)(17)(18)(19)(20)(21). Recent studies of reproductive and placental tissues from scrapie-infected pregnant sheep demonstrated that PrP Sc accumulates at the fetalmaternal interface (the placentome) and proposed that scrapie is not transmitted in utero, but may be transmitted from infected dams to their scrapie susceptible lambs during the perinatal period by exposure to infectious placental tissues (9).…”
mentioning
confidence: 99%
“…In sheep, PrP Sc or scrapie infectivity is present primarily in tissues of the central and peripheral nervous system, lymphoreticular system, and placenta (9,(14)(15)(16)(17)(18)(19)(20)(21). Recent studies of reproductive and placental tissues from scrapie-infected pregnant sheep demonstrated that PrP Sc accumulates at the fetalmaternal interface (the placentome) and proposed that scrapie is not transmitted in utero, but may be transmitted from infected dams to their scrapie susceptible lambs during the perinatal period by exposure to infectious placental tissues (9).…”
mentioning
confidence: 99%
“…Macrophages containing PrP Sc have been detected in ovine Peyer's patches, 46 other secondary lymph nodes of variant CJD patients, 47 and the spleen of mice. 48 In the spleen, PrP-positive cells were entirely CD14-positive macrophages (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sheep deliberately challenged with BSE display PrP Sc in a broad range of tissues including the lymphoid system, parts of the digestive tract and in the peripheral nervous system [29]. The distribution of infectivity in these BSE affected sheep is similar to that observed in sheep of similar PrP-genotype infected with scrapie [9, 42,62,63]. The spread of PrP Sc to the lymphoid organs is thought to be mediated by the lymphoreticular system.…”
Section: Introductionmentioning
confidence: 90%